Labor migration: current and perspective challenges for Ukraine - Cherevko, Heorhiy (Technological and Economic Development of Economy, 2022)
The main purpose of this study was to analyze the labor resources migration phenomenon from Ukraine in the context of theoretical basics of it generalization and against the background of its evolution and world trends, to identify its specific features, real consequences and possible perspectives regarding the regulation possibility taking into account the specifics of the nature and structure of this phenomenon in this country. The research methodology is formed on the basis of the classic economic theory of migration in combination with the behavioral approach and the interpretation of human as homo oeconomicus. Methods were used in the research process: dialectical, historical and semantic analysis, method of theoretical generalization and scientific abstraction, induction and deduction, monographic, graphic, statistical and analytical. The main findings are related to the detection of the tendency to increase the scale of labor migration from Ukraine even under conditions of pandemic, the identification of threats and harms connected with this phenomenon. Substantiated recommendations for eliminating the threats and harms of international labor migration from Ukraine may have practical applications. The originality of the article is determined by its timeliness and by diversified set of used sources of information, what together forms its value as well.First published online 28 December 2021